2019
DOI: 10.1007/s12671-019-01279-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Mindfulness Meditation Training Enhance Executive Control? A Systematic Review and Meta-Analysis of Randomized Controlled Trials in Adults

Abstract: Objectives: Over the last years, mindfulness meditation has been claimed to be effective in enhancing several cognitive domains, including executive control. However, these claims have been mostly based on findings pertaining to case-control and cross-sectional studies, which are by nature unable to reveal causal relationships. Aiming to address this issue, we set out to conduct the first quantitative assessment of the literature concerning mindfulness meditation as an enhancer for executive control considerin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 73 publications
(82 reference statements)
5
70
1
1
Order By: Relevance
“…Mindfulness training preserved sustained attention on the SART in the mindfulness group relative to the coding group. This finding aligns with prior behavioral studies reporting enhanced cognitive control after mindfulness training in children (Britton et al, 2014; Felver et al, 2017; Flook et al, 2010; Lawler et al, 2019; Leonard et al, 2013; Quach et al, 2016; Salmoirago‐Blotcher et al, 2019; Schonert‐Reichl et al, 2015;Semple et al, 2010; Sidhu, 2012) and adults (Cásedas et al, 2019; Moore & Malinowski, 2009). These RCTs demonstrated improved attentional ability measured by task performance or parent/teacher‐reported questionnaires in typically developing children and adolescents (Felver et al, 2017; Schonert‐Reichl et al, 2015), in children with ADHD (Sidhu, 2012) or reading difficulties (Semple et al, 2010; Sidhu, 2012), and in incarcerated adolescents (Leonard et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Mindfulness training preserved sustained attention on the SART in the mindfulness group relative to the coding group. This finding aligns with prior behavioral studies reporting enhanced cognitive control after mindfulness training in children (Britton et al, 2014; Felver et al, 2017; Flook et al, 2010; Lawler et al, 2019; Leonard et al, 2013; Quach et al, 2016; Salmoirago‐Blotcher et al, 2019; Schonert‐Reichl et al, 2015;Semple et al, 2010; Sidhu, 2012) and adults (Cásedas et al, 2019; Moore & Malinowski, 2009). These RCTs demonstrated improved attentional ability measured by task performance or parent/teacher‐reported questionnaires in typically developing children and adolescents (Felver et al, 2017; Schonert‐Reichl et al, 2015), in children with ADHD (Sidhu, 2012) or reading difficulties (Semple et al, 2010; Sidhu, 2012), and in incarcerated adolescents (Leonard et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Systematic reviews of mindfulness RCT studies have reported that mindfulness training frequently improves cognitive control in both children and adults (Cásedas, Pirruccio, Vadillo, & Lupiáñez, 2019; Chiesa et al, 2011; Mak et al, 2018). A meta‐analysis of RCTs employing mindfulness‐based interventions in adults found a moderate but significant improvement of cognitive control, specifically in attention and memory (Cásedas et al, 2019). For children and adolescents, 8 out of 10 RCTs reported that mindfulness training improved cognitive control and attentional abilities (with an additional trend in a ninth study) (Britton et al, 2014; Felver, Tipsord, Morris, Racer, & Dishion, 2017; Flook et al, 2010; Lawler, Esposito, Doyle, & Gunnar, 2019; Leonard et al, 2013; Quach, Jastrowski Mano, & Alexander, 2016; Salmoirago‐Blotcher et al, 2019; Schonert‐Reichl et al, 2015; Semple, Lee, Rosa, & Miller, 2010; Sidhu, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent meta-analysis across 13 RCTs (n = 1,112) observed that MBIs had moderate effects on WM and inhibition, but a negligible effect on shifting among adults (Cásedas, Pirruccio, Vadillo, & Lupiáñez, 2020). In the other meta-analysis, across 17 studies (n = 1,762)…”
Section: Trialsmentioning
confidence: 99%
“…Some studies have, however, suggested more nuanced and selective effects in awareness, e.g., improvement in object detection but not in attention or improvement in the attentional effort instead of ability (Anderson, Lau, Segal, & Bishop, 2007;Jensen, Vangkilde, Frokjaer, & Hasselbaich, 2012). A recent review found a small-to-medium effect (g = 0.34 [0.16, 0.51]) of mindfulness meditation training in enhancing executive control (Cásedas, Pirruccio, Vadillo, & Lupiáñez, 2020), whereas a review on neuropsychological outcomes found no overall support for attention or executive function improvements (Lao, Kissane, & Meadows, 2016). Some independent practice is considered necessary for mindfulness intervention effects to appear among adolescents (Huppert & Johnson, 2010;Zenner, Herrnleben-Kurz, & Walach, 2014) even if the length of the practice can be distinctly shorter than among adults (5-10 min) (Meiklejohn et al, 2012;Zack, Saekow, Kelly, & Radke, 2014).…”
Section: Introductionmentioning
confidence: 99%